"Is there any time left for walking?" Physical activity implications of suburban commuting in the Barcelona metropolitan region. Issue 2 (3rd July 2019) - Vich, Guillem; Marquet, Oriol; Miralles-Guasch, Carme
ABSTRACT: The present study delves into the explanatory factors of the walking patterns of residents in metropolitan regions, who tend to be pressed for time when travelling to their daily destinations or activities. We particularly focus on the effects of the commuting distance on the amount of walking that can be achieved, which has health, socioeconomic and environmental implications. This study confirms the potential benefits of using smartphone tracking data to examine walking patterns. To enable this, a smartphone tracking application was developed to obtain accurate mobility data from a group of adults ( n = 93) residing in the Barcelona Metropolitan Region (Spain) and have to commute to a suburban university campus that can only be reached by using motorized transport modes. The results highlight the commuting distance and employment status as strong determinants of the amount of walking time achieved by this study group. Moreover, it was determined that among transit users, the commuting distance of male commuters was negatively associated with walking when compared with female transit users, whereas explanatory factors for private transport users bore insignificant results. Smartphone devices proved their potential as an effective and useful source of data in transportation and health research.